Peran, Desain, dan Pengelolaan Ruang Komunal dalam Mendukung Kualitas Hidup Masyarakat Permukiman Informal Bantaran Sungai - Mas Joni; M Syauqi Hikam Fayazid; Noor Cholis Idham (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Informal riverbank settlements in urban areas generally face limited space, high density, and low environmental quality, which impacts the quality of life of their residents. In this context, communal spaces are an important element that has the potential to improve community welfare. This study aims to explore the role of communal spaces in improving the quality of life of communities in Serangan Village (Winongo River) and Code-Terban Village (Code River), and to identify the principles of their design and management. The method used is a qualitative approach with a case study strategy. Data were collected through literature studies, field observations, in-depth interviews with various community groups, and document analysis. Data were analyzed descriptively through a process of reduction, categorization, and thematic interpretation. The results show that communal spaces play an important role as social infrastructure in improving the quality of life through 5 main dimensions: (1) Social, (2) Health & Psychological, (3) Physical, (4) Economic, and (5) culture and education. Communal spaces strengthen social cohesion and social capital, provide relaxation spaces that support mental health, encourage physical activity and environmental improvement, and support community-based local economies. In addition, communal spaces also function as a forum for cultural preservation and social learning. The discussion shows that the success of communal spaces is determined by the design criteria that are Flexible, Comfortable, Adaptive, and participatory management. Integration of social and economic functions and optimization of unused spaces are important factors in increasing the sustainability of spaces. This study concludes that communal spaces are an effective strategy in community-based development to improve the quality of life of informal settlement communities, and have the potential to be replicated in similar contexts.